2015
DOI: 10.1016/j.coviro.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Relating structure and function of viral membrane-spanning miniproteins

Abstract: Many viruses express small hydrophobic membrane proteins. These proteins are often referred to as viroporins because they exhibit ion channel activity. However, the channel activity has not been definitively associated with a biological function in all cases. More generally, protein-protein and protein-phospholipid interactions have been associated with specific biological activities of these proteins. As research has progressed there is a decreased emphasis on potential roles of the channel activity, and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…SARS-CoV-2 E protein is a hydrophobic 75-residue protein with an amino acid sequence nearly identical to that of SARS-CoV E protein ( S1 Fig ) [ 12 ]. Since E protein is a viral membrane-spanning miniprotein [ 16 ], a recurring question is whether it is a viroporin. Although ion-channel activity has been detected in a variety of preparations it lacks sequence homology with any of the well-established viroporins, and there is a notable absence of charged sidechains on the interior of a pore formed by pentamers of the protein in membrane environments [ 9 , 10 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 E protein is a hydrophobic 75-residue protein with an amino acid sequence nearly identical to that of SARS-CoV E protein ( S1 Fig ) [ 12 ]. Since E protein is a viral membrane-spanning miniprotein [ 16 ], a recurring question is whether it is a viroporin. Although ion-channel activity has been detected in a variety of preparations it lacks sequence homology with any of the well-established viroporins, and there is a notable absence of charged sidechains on the interior of a pore formed by pentamers of the protein in membrane environments [ 9 , 10 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This reduced size might reflect the need to take optimal advantage of the limited sequence information encoded in compact viral genomes, as already observed for other viral proteins (for review see ref. 31 ). On the other hand, it has been previously suggested that viral PDFs might exhibit specific distinct substrate specificity compared to bacterial PDFs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…While solution-state NMR and X-ray crystallography was widely used on small viral membrane proteins in detergent, solid-state NMR has the advantage that the proteins can be investigated in lipids, which are closer mimics of native membranes. Solid-state NMR investigations were first initiated on small viral membrane proteins, also called “viral membrane-spanning mini-proteins” [ 117 ], often using oriented samples to obtain spectra [ 118 ]. In this context, HIV-1, influenza and parainfluenza virus fusion peptides of ~20 amino acids have been studied early on [ 119 , 120 , 121 , 122 ] to reveal the structure and orientation behavior of these fragments in lipid bilayers under conditions mimicking membrane fusion.…”
Section: Examples Of Solid-state Nmr Studies On Viral Proteinsmentioning
confidence: 99%